Aggravated pulmonary injury after subarachnoid hemorrhage in PDGF-B(ret/ret) mice - Pan, Pengyu (Chin Neurosurg J, 2020)
BACKGROUND: Recent advances in surgical and neuroprotective strategies could effectively manage the pathophysiological progression of subarachnoid hemorrhage (SAH). However, pulmonary dysfunction frequently occurs in SAH patients with an increased risk of unsatisfactory outcomes. Based on the similar microvascular structures in the blood-air barrier and blood-brain barrier and possible brain-lung crosstalks, we believe that pericytes may be involved in both neurological and pulmonary dysfunction after SAH. METHODS: In our experiments, platelet-derived growth factor B (PDGF-B) retention motif knockout (PDGF-B(ret/ret)) mice and adeno-associated virus PDGF-B were employed to show the involvement of pericyte deficiency and PDGF-B expression. Neurological score, SAH grade, hematoxylin-eosin staining, and PaO2/FiO2 ratio analysis were performed to evaluate the neurological deficits and pulmonary functions in endovascular perforation SAH models at 24 h after surgery, as well as western blotting and immunofluorescence staining for underlying molecular expressions. RESULTS: We found that neonatal PDGF-B(ret/ret) mice exhibited pulmonary atelectasis 12 h after birth. Further investigation showed a decrease in PaO(2)/FiO(2) and lung-specific surfactant proteins in adult PDGF-B(ret/ret) mice. These dysfunctions were much worse than those in wild-type mice at 24 h after SAH. PDGF-B overexpression alleviated pulmonary dysfunction after SAH. CONCLUSIONS: These results suggested pulmonary dysfunction after SAH and the pivotal role of PDGF-B signaling for the pathophysiological process and future therapeutic targets of pulmonary injury treatment after SAH. Further studies are needed for pathophysiological investigations and translational studies on pulmonary injuries after SAH.